A disappearing world - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
A team of people is travelling through Africa. The team wants to photograph and document the wildlife of this beautiful part of the world. They want to do it before this beauty disappears, or goes away, forever
Video and audio on DVD
Title from container
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography